Caracterização nutricional e cinética da degradação ruminal da aveia branca IPR 126 ( Avena Sativa L. CV. IPR 126), sob diferentes níveis de adubação nitrogenada - Kölln, Raquel Suzane (2017)
The objective of the present study was to estimate the bromatological composition and the parameters related to the in vitro gas production kinetics of oat IPR 126, fertilized with different nitrogen rates (0, 60, 120, 240 kg ha-1 of N), in two Years of production (2013- 2014). The chemical composition was determined: dry matter (DM), crude protein (PB), ethereal extract (EE), neutral detergent fiber (aFDNom), acid detergent fiber (FAD), insoluble protein (LDA), Total Carbohydrates (CT), Nonfibrous Carbohydrates (CNF) and Soluble Carbohydrates (CHOs) of cultivar IPR 126, as well as the estimation of the parameters of the bicompartmental model for kinetics of Production of gases (Vf1, k1, Vf2 e k2 e L). Nitrogen fertilization influenced only PB and CT contents. In relation to the bromatological variables, LDA, CT, CNF and CHOs were significantly higher in 2013. MM, aFDN and PB were higher in 2014. In 2013, comparing the performed cuts, most of the bromatological variables did not present a significant difference, except for LDA and CHOs. In the year 2014, the observed values of the bromatological variables were significantly higher in the 1st cut for EE, CNF and CHOs. For MM, aFDN, LDA and PIDA were higher in the 2nd cut. There was a significant effect in relation to the degradation kinetic parameters in vitro gas production, with the exception of L. In the comparison of the years of cultivation, k1, Vf2 and k2, increased in 2014. However, Vf1 presented a reduction in 2014. In the year of 2013 comparing the cuts performed, there was a significant effect only for rates k1 and k2. No significant differences were found in any parameter, analyzing the cuts of 2014. The white Oat IPR 126 has a good potential to be cultivated in the southwestern region of Paraná, because it responds to nitrogen fertilization and manages to express its forage potential even with unfavorable climatic conditions. The high levels of crude protein found in this work indicate an imbalance between.